EVALUASI KESIAPAN GURU SEKOLAH DASAR TERHADAP PELAKSANAAN KURIKULUM MERDEKA DI SD NEGERI CIKARET 2 - Destikasari; Hendro Prasetyo (STKIP Subang, 2025)
This study aims to evaluate the readiness of elementary school teachers at SD Negeri Cikaret 2 in implementing the Independent Curriculum (Kurikulum Merdeka). The research was motivated by the need to understand teachers’ level of preparedness in adapting to curriculum changes that emphasize student-centered learning, differentiated instruction, and project-based learning. The study employed a descriptive qualitative method supported by quantitative data to provide a comprehensive overview of teacher readiness. Data were collected through questionnaires, interviews, and classroom observations involving ten teachers who actively participate in the implementation of the Independent Curriculum. The results indicate that the overall readiness of teachers at SD Negeri Cikaret 2 falls within the moderate category. Teachers show a positive attitude and willingness to adopt innovative learning models, but face challenges related to digital literacy, mastery of learning assessments, and limited access to training. Institutional support from the school and local education authorities is also identified as a crucial factor influencing teachers’ readiness. The study concludes that continuous professional development and improvement in school facilities are essential to enhance teachers’ competence and ensure the effective implementation of the Independent Curriculum.